Faktor-Faktor Penentu Financial Distress Pada Perusahaan Consumer Services Yang Terdaftar Di Bursa Efek Indonesia Tahun 2021 (Fakultas Ekonomi Universitas Gresik, 2023)
Determining the factors that cause companies to experience financial distress is important. Current Ratio (CR), Debt To Asset Ratio (DAR) and Return On Assets (ROA) are factors that can detect a company experiencing financial distress. Consumer services companies experienced a decline in earnings per share. This study aims to analyze the influence of Current Ratio (CR), Debt To Asset Ratio (DAR) and Return On Assets (ROA) which can cause financial distress in consumer services companies. This research is in the form of quantitative research, where the data obtained is then processed using SPSS software. The analytical method used is logistic regression. The results of this study indicate that the Current Ratio (CR) has no effect on financial distress, Debt To Asset Ratio (DAR) has a positive effect on financial distress and Return On Assets (ROA) has a negative effect on financial distress.